Eclipse and Wind Phenomenon in The Perspective of Hadith Aqidah - Febriansyah; Putri Dela Sari; Muhammad Faried Al-Fithri; Anisa Nabila Tuzzahidah; Muhammad Tauhid (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
This paper examines how Hadiths about natural phenomena, especially eclipses and wind, can strengthen the aqidah of Muslims. The study of hadiths about eclipses and wind is reinforced by the interpretation of the Qur'an, the opinions of scholars, and some scientific opinions to prove its truth. This paper uses a qualitative method with the type of library research and data analysis techniques in the form of descriptive analytical. Thus, this paper concludes that the eclipse phenomenon in the hadith perspective is a sign of God's power that is not a myth and is not caused by someone's death. Meanwhile, the wind phenomenon contained in the hadith shows the power of God sent to His servants, regardless of whether the wind sent by God is a mercy or not. In this case, the appropriate attitude taught by the Prophet is to trust and pray for what Allah has determined. This conclusion indicates the existence of creedal values contained in the Hadith, namely the value of faith in the Last Day, the importance of prayer and supplication, the value of tawakal, and the value of ethics in speaking.